The Needs of Elementary School Teachers in Literacy Learning on Reading Comprehension Competence - Ayu Nur Azizah; Ida Zulaeha; Panca Dewi Purwati; Woro Sumarni; Putut Marwoto (AL-ISHLAH: Jurnal Pendidikan, 2022)
Learning will be effective if the teacher understands the needs of learning well. The purpose of this study was to explore the needs of teachers in literacy learning on reading comprehension competence in elementary schools. The method used in this research is exploratory qualitative which was conducted at the State Elementary School in Central Magelang Sub-District, Magelang City, Central Java Province, Indonesia. The results of the study indicate that there are several problems in literacy learning of reading comprehension competence so teachers need several learning innovations as solutions, namely in the learning model by combining problem-based learning models with the SQ3R model, in teaching materials by developing integrated teaching materials with innovative learning models, and on the assessment instrument by developing an assessment instrument oriented towards high order thinking skills (HOTS). The results of this needs analysis will be used to conduct further research as a form of literacy learning innovation in reading comprehension competence.